Drug resistance in parasites: A review of mechanisms, drivers, and mitigation strategies - Jan Clyden Tenorio (Microbes and Infectious Diseases, 2025)
Background: Drug resistance among parasitic pathogens is a pressing public health concern. This review highlights the emergence of resistance among parasites, its impacts, key drivers and potential solutions. The objective of this review is to provide an overview of the harms and risks associated with drug resistance among parasites of public and veterinary health concerns. Resistance is often attributed to mutations in target proteins, altering their binding and efficacy. Other factors contributing to resistance include increased drug exposure due to self-medication, genetic diversity of parasites, and environmental factors like climate change. The emergence of these resistance-associated mutations may lead to catastrophic consequences, like inefficient drug-based control and elimination programs, rebounds in cases, and the widespread occurrence of severe pathological consequences due to unchallenged infections. Strategies to address drug resistance include surveillance, innovative population-based drug administration methodologies, vaccine development, and non-pharmaceutical interventions (i.e., improved sanitation and hygiene, and community health education). Addressing drug resistance requires a multi-faceted approach to prevent its further spread and ensure effective parasite control and elimination.